Acupuncture for diminished ovarian reserve: Protocol for a systematic review and meta-analysis. Issue 34 (August 2019) - Ma, Ruihong; Song, Jiayi; Si, Jinhua; Liu, Yan; Li, Xinyun; Cheng, Rui; Hu, Zuxian; Xia, Tian; Zhai, Jingbo
Abstract: Background: The choice of treatments for diminished ovarian reserve (DOR) still remains a challenging clinical problem in reproductive medicine. Acupuncture could be beneficial for patients with DOR. This study aims to systematically investigate the efficacy and safety of the acupuncture for women with DOR. Methods: We will search electronic databases including PubMed (1946 to present), EMBASE (1974 to present), Cochrane Central Register of Controlled Trials (CENTRAL, all years), Web of Science (1900 to present), Chinese Biomedical Literatures Database (CBM, 1978 to present), China National Knowledge Infrastructure (CNKI, 1979 to present), WANFANG Data (from 2000 to present) to identify potentially eligible studies. Only randomized controlled trials (RCTs) will be included. Experimental interventions include traditional or contemporary acupuncture. Control interventions include no treatment, sham acupuncture, placebo acupuncture, or another active therapy. The primary outcomes include ongoing pregnancy rate and serum anti-Müllerian hormone level. A meta-analysis will be used to estimate a pooled intervention effect if possible. Results: The results will be published in a peer-reviewed journal. Conclusion: The findings will provide further evidence for the management of DOR. PROSPERO registration number: CRD42018114385. Abstract : Supplemental Digital Content is available in the text